Desarrollo de un sistema DSS de inteligencia de negocios utilizando ORACLE APEX 42.5 y ORACLE WAREHOUSE BUILDER para la empresa Redpartiner - Troya Ospina, Gabriel Antonio (2016)
The main purpose of this project is to develop a system to support decision making (DSS) for the financial area of the company Red Partner in order to change the current situation which is characterized by inconsistent, isolated information without categorization. Initially, it is required an analysis of the theoretical framework in order to expose all the knowledge researched about business intelligence, that is applied in this project. Within the theoretical framework is information about the concepts and fundamentals of business intelligence, design and development methodologies and tools. The first phase consists on the analysis for the selection of methodologies applied in this project. The main features of the options involved in the analysis are presented in addition to the parameters that justify the selection of a design and development methodology. Once the selection of methodologies has been made, the next phase begins with the system requirement analysis which specifies everything that must be achieved in the design and development of data warehouse and application to manage this data model. Additionally, the process of implementation of the system is explained as well as the preparation of technical documentation and user training. Finally, the last phase of this project is about the definition of conclusions and recommendations on which the objectives achieved are explained. The implemented solution is presented, demonstrating the added value acquired by the company Red Partner proving that a better use of data allows the organization to generate knowledge that will enable them to be more competitive with their business due to better decisions taken.